32.6k views
1 vote
Which shows equivalent expressions?

a2+3b-2a2=3a2+3b-4a2
a2+3b-2a2=3a2+4b-4a2
-a2+3b-2a2=3a2+3b
-a3+3b+2a2=3a2+4b-2a2

User Splicer
by
5.0k points

2 Answers

4 votes

You can sum terms that involve the same literal expressions:


a^2+3b-2a^2=3a^2+3b-4a^2 \iff -a^2+3b=-a^2+3b


a^2+3b-2a^2=3a^2+4b-4a^2 \iff -a^2+3b = -a^2+4b


-a^2+3b-2a^2=3a^2+3b \iff -3a^2+3b = 3a^2+3b


-a^3+3b+2a^2=3a^2+4b-2a^2 \iff -a^3+3b+2a^2=a^2+4b

So, the only expression whose left and right hand sides are equal is the first.

User Mkeremguc
by
5.4k points
3 votes

Explanation:

a2 + 3b - 2a2 = 3a2 +3b -4a2

User Bira
by
4.8k points